Redesain Bangunan Teater Pertunjukan Taman Festival Bali Dengan Pendekatan Adaptive Reuse - I Putu Dika Mustika; I Gede Adi Setia Darma; I Kadek Merta Wijaya (Universitas Medan Area, 2022)
Bali Festival Park is a tourist place that is very loved by the Balinese people and also tourists, both foreign tourists, and local tourists. This place presents a variety of rides and facilities that are quite complete for visitors to spend their free time. However, at this time the Bali Festival Park has begun to be abandoned by the public and tourists, this has made some buildings that can still be used physically abandoned. The building is an icon of the main building has a unique roof shape and also has an adequate area, besides that this building also still has a solid structure. The building that faces directly towards the sea also has its own added value, which is to offer a unique view of the beach. Currently, the world of work is very important in regional economic growth so it is very important to provide good and comfortable facilities for workers to increase their productivity so that the function of the Taman Festival Bali performance theater building becomes a Co-Working space using an adaptive approach. reuse will be a good choice because, in addition to being able to work together with various companies, employees can also indulge themselves with the scenery and existing facilities. This research itself aims to create a comfortable place for companies as a place to be able to provide peace for their employees and can share work experiences with other companies. The method used is descriptive qualitative through studies and descriptions of architectural problems and formulating solutions in the form of schematic designs. The results of this study are the elements of space that are presented in the form of floor plans, 3D Interior, and exterior.